Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Rethinking art's histories, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme

Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Artistes femmes: la parenthèse enchantée: XVIIIe-XIXe siècles - Sofio, Séverine (CNRS éditions, 2016)
Entre 1750 et 1850, l'univers des beaux-arts connaît de profondes mutations, dont l'une des conséquences est la banalisation d'une image positive de la dame artiste. Progressivement, des barrières s'abaissent, des contraintes se desserrent et la pratique de la peinture est rendue plus accessible aux femmes. S'ouvre alors une période de créativité foisonnante associée aux noms--parfois oubliés aujourd'hui--d'Elisabeth Vigée-Lebrun, Adélaïde Labille-Guiard, Marie-Guillemine Benoist, Marguerite Gérard, Constance Mayer, Victoire Jaquotot, Lizinka de Mirbel, Rosa Bonheur ...
Keywords: 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; périodes historiques; régions géographiques; thématiques

Chair à canons: Photographie, discours, féminisme - Solomon-Godeau, Abigail; Poupard, Laure; Jones, Julie (Écriture photographique (Paris), 2016)
a 4e de couverture indique : [L'auteure] est aujourd'hui l'une des plus importantes théoriciennes de la photographie. Historienne de l'art, critique et professeur émérite à l'université de Californie à Santa Barbara, ses travaux portent principalement sur la théorie du genre, les études féministes, la culture visuelle en France au XIXe siècle, l'histoire de la photographie et l'art contemporain. ... le présent recueil réunit pour la première fois en langue française un ensemble d'essais parmi les plus significatifs de cette auteure majeure. ... l'ouvrage propose une première partie sur les discours de l'histoire de la photographie, une deuxième sur les pratiques documentaires et une troisième sur la représentation du féminin.
Keywords: 1900-1999; Photographie documentaire; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire de la photographie; histoire et politique; photographie; premier cycle; périodes historiques; représentation des femme*; thématiques